To Hold the Epoch’s Duty Together, to Promote the Development of World Education Together - Ma, Wen (Advances in Social Sciences Research Journal, 2017)
This paper reviews books and articles on globalization and education. It begins with a brief overview of the issues facing humankinds, focusing specifically on cultural globalization. The paper then moves on to examine how education globalisation is viewed and carried out in relation to the topic of culture and education. It also examines the conflicts that are described within the fields of educational studies, as well as the actions that can be used to undertake in an era of globalization.